The Effectiveness of Education on the Impact of Early Marriage from a Religious Health and Legal Perspective in Tamalate Village Manuju Distric Gowa Regency - Nabila, Nabila Fauziah; Salwa, Putri; Abhar, Andi; Andi Nida’ul Hasanah,; Hidayat, Taufik (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2025)
Early marriage is a multidimensional problem that has significant impacts on health, social, psychological, legal, and human rights aspects, especially for girls. This study aims to determine the effectiveness of education about the impact of early marriage from a religious, health, and legal perspective in increasing community knowledge in Tamalate Village, Manuju District, Gowa Regency. The research method used is a quantitative approach with a pre-test and post-test design without a control group. The sampling technique used was random sampling, with a total of 30 respondents. The data collection instrument was a questionnaire classified into three levels of knowledge: less, sufficient, and good. Data analysis was performed using the Wilcoxon test because the data were not normally distributed. The results showed a significant increase in knowledge after the education, as indicated by a p-value of 0.020 (<0.05). The average knowledge score increased from 2.50 before the intervention to 3.00 after the intervention. This finding indicates that the education provided was effective in increasing public understanding of the dangers and consequences of early marriage, both from a religious, health, and legal perspective. However, the results also indicate that there is still room for optimization of the educational intervention, considering that the increase in scores has not yet reached the maximum level. Factors such as duration, delivery method, respondent background, and individual motivation can influence the overall effectiveness of the education.